Effects of meal regularity and snacking frequency on irritable bowel syndrome - Ajabnoor, Sarah M. (Frontiers in Public Health, 2025)
BackgroundDietary practices often trigger irritable bowel syndrome (IBS) symptoms. This study primarily aimed to identify and compare the frequency of different eating behaviors in free-living adults in Saudi Arabia with either self-diagnosed IBS or IBS diagnosed based on Rome IV criteria. The study also examined how irregular eating affects IBS symptom severity.MethodsThis cross-sectional study included 204 adults, 106 (52%) with self-diagnosed IBS and 98 (48%) with Rome IV-defined IBS. All participants completed a questionnaire assessing sociodemographic characteristics, IBS diagnosis (using Rome IV criteria), IBS symptom severity scale (IBS-SSS), and eating patterns.ResultsIrregular eating patterns were similarly reported in both groups. Dietary practices such as not eating meals on a regular schedule and skipping breakfast were reported by approximately 20 and 30% of the participants in each group, respectively. In the regression analysis, frequent snacking was independently associated with lower IBS-SSS, while chewing difficulty, chronic conditions, and type of IBS diagnosis predicted higher severity (adjusted R2 = 0.260, p < 0.001).ConclusionFrequent snacking is linked to reduced IBS symptom severity; however, there is a need to consider dietary behaviors alongside comorbid conditions and type of IBS diagnosis in IBS management. Further research into self-diagnosed IBS (a widely prevalent patient group) is required to better understand how these individuals differ from those with a formal diagnosis.